The management of people and subjects with ADHD in the labor market - Tais Gonçalves Alves, Daniela; Carlos Souza dos Santos, Felipe; de França Ramos, Jovanna; Beatriz da Silva, Nataly; Borges Figueredo, Natieli; Luiz Carrino , Adauto; Estrella Pagliuso, Marcia (Seven Editora, 2023)
Currently, one of the most common mental disorders in the social environment is attention deficit hyperactivity disorder (ADHD). Thus, this paper presents as problematization the questioning about the role and importance of people management in relation to subjects with ADHD in the labor market. Faced with this problem, we awakened this study with the objective of showing the importance of good people management within the corporate environment and understanding the impact that employees with ADHD has on the organization.  Thus, as a methodological path, we intensified the obtaining of the information presented, contemplating a database with a focus on bibliographic and electronic research, interposing the basis in books by renowned authors and articles on the respective theme, as well as a critical and analytical look at this perspective and contemporary society. Moreover, with the research esplanade in this article, we expanded to new studies and looks at this theme, interposing the categorization related to ADHD and the difficulties of insertion of this population from the labor market, as well as in understanding their differences and inserting them in the institution, transforming it into a more inclusive place, with opportunities and free of prejudices.   DOI: https://doi.org/10.56238/tfisdwv1-068